Hubungan merokok dengan saturasi oksigen pada pegawai di fakultas kedokteran universitas Sam Ratulangi Manado - Septia, Nindirah; Wungouw, Herlina; Doda, Vanda (e-Biomedik, 2016)
Abstract: Smoking is an overt behavior in which smokers inhale tobacco rolls. The degree of smoking can be determined based on the Brinkman index. Global Adults Tobacco Survey (GATS) estimates there are currently 7.9 billion adults who are actively smoking and 3.5 billion people are exposed to secondhand smoke in the workplace. This research aims to identify oxygen saturation of smokers and the correlation between smoking and oxygen saturation of administration staffs in the Medical Faculty of Sam Ratulangi University Manado. This research was a cross sectional study that was conducted on 30 administration staffs at the Faculty of Medicine, University of Sam Ratulangi. The correlation analysis was carried out using Kruskall-Wallis. Most respondents were mild smokers (63.33%) with the average oxygen saturation 98.37. Moderate Smokers have an average oxygen saturation of 97.86, and heavy smokers 96.25. All respondents had an average oxygen saturation of 97.97. All respondents are still categorized as having normal oxygen saturation (95-100%). Conclusion: There is a significant correlation between smoking and oxygen saturation. The more severe the degree of smoking, the lower level of oxygen saturation obtained in the blood.Keywords: smoking, oxygen saturation, administration staff.Â Abstrak: Merokok merupakan overt behavior dimana perokok menghisap gulungan tembakau. Derajat merokok dapat ditentukan berdasarkan Index Brinkman. Global Adults Tobacco Survey (GATS) memperkirakan terdapat 7,9 milyar orang dewasa saat ini perokok aktif dan 3,5 milyar orang terpapar asap rokok di tempat kerja. Penelitian ini bertujuan untuk mengetahui saturasi oksigen pada perokok dan hubungan merokok dengan saturasi oksigen pada pegawai di Fakultas Kedokteran Universitas Sam Ratulangi Manado. Penelitian ini bersifat observasional analitik dengan rancangan penelitian potong lintang yang dilakukan pada 30 pegawai di Fakultas Kedokteran Universitas Sam Ratulangi Manado dengan uji statistik Kruskal-Wallis. Penelitian ini memiliki nilai p < 0,05. Responden terbanyak adalah perokok derajat ringan (63,33%) dengan saturasi oksigen rata-rata 98,37. Perokok derajat sedang memiliki saturasi oksigen rata-rata 97,86 sedangkan perokok derajat berat 96,25. Seluruh responden memiliki saturasi oksigen rata-rata 97,97. Seluruh responden masih termasuk kategori saturasi oksigen baik (95-100%). Simpulan: Terdapat hubungan yang signifikan antara merokok dengan saturasi oksigen. Semakin berat derajat merokok maka semakin rendah kadar saturasi oksigen dalam darah. Kata kunci: merokok, saturasi oksigen, pegawai.